Antibiotic treatment for children hospitalized with community‐acquired pneumonia after oral therapy. Issue 5 (4th February 2015) - Breuer, Oded; Blich, Ori; Cohen‐Cymberknoh, Malena; Averbuch, Diana; Kharasch, Sigmund; Shoseyov, David; Kerem, Eitan
Summary Objective To compare the outcome of treatment with narrow spectrum versus broad spectrum antibiotics in children hospitalized with community‐acquired pneumonia (CAP) who received oral antibiotic treatment prior to their hospitalization. Design, Setting, and Patients A review of all previously healthy children from 3 months to 18 years with non‐complicated CAP who received an oral antibiotic course in the community and were admitted from 2003 to 2008 to our pediatric departments. Main Outcome Measures Clinical course and outcome parameters were compared for treatment with narrow and broad spectrum antibiotics. Results Of the 337 children admitted with non‐complicated CAP after an oral antibiotic treatment course in the community, 235 were treated with broad spectrum, and 102 with narrow spectrum antibiotics. The two groups were similar regarding age, sex, days of fever prior to admission, type of preadmission oral antibiotic treatment, and laboratory indices at admission (P > 0.1). The broad spectrum‐treated group had significantly better outcomes in terms of number of febrile days (1.2 ± 1.1 vs. 1.7 ± 1.6, P < 0.001), number of days treated with intravenous antibiotics (3.1 ± 1.3 vs. 3.9 ± 2.0, P < 0.001), and days of hospitalization (3.5 ± 1.5 vs. 4.2 ± 2.0, P < 0.001). The odds ratio for remaining hospitalized at 72 hr and 7 days was significantly higher for the narrow spectrum group (2.0 and 5.5 respectively, P < 0.05). Conclusions In previously healthy children hospitalized with CAP after oral antibiotic treatment in the community treatment with broad spectrum antibiotics showed better outcome. Prospective studies are needed for appropriate recommendation. Pediatr Pulmonol. 2015; 50:495–502. © 2015 Wiley Periodicals, Inc.